2020
DOI: 10.1016/j.jaip.2020.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Acute urticaria with angioedema in the setting of coronavirus disease 2019

Abstract: Conflicts of interest: The authors declare that they have no relevant conflicts of interest. Informed consent: The patient gave written informed consent for publication (both clinical information and images).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…All symptoms except cough improved after 2 days of methylprednisolone and diphenhydramine. Moreover, Adeliño and colleagues 7 reported a 30-year-old woman who developed acute urticaria and angioedema 11 days after the onset of COVID-19 respiratory symptoms. Those manifestations quickly resolved after she received 3 days of ebastine 10 mg.…”
Section: Discussionmentioning
confidence: 99%
“…All symptoms except cough improved after 2 days of methylprednisolone and diphenhydramine. Moreover, Adeliño and colleagues 7 reported a 30-year-old woman who developed acute urticaria and angioedema 11 days after the onset of COVID-19 respiratory symptoms. Those manifestations quickly resolved after she received 3 days of ebastine 10 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an extensive review of 997 patients from 9 different countries analyzed by Jia et al found that approximately 22% of patients had urticarial eruptions [4••]. Urticaria with or without angioedema in the setting of confirmed or highly suspected COVID-19 infection has been observed in several reports and case series [2,5,[39][40][41][42][43][44][45][46][47]. Similar to other viral infections, urticarial rash may precede or occur simultaneously with COVID-19 systemic manifestations (i.e., fever, cough) and last for several days [5,39,43,44,47,48].…”
Section: Urticaria and Angioedemamentioning
confidence: 99%
“…After eliminating the overlaps between the two search engines, we were left with 23 works investigating the relationships between SARS-CoV-2 infection and urticaria. Of these, 18 reported cases of urticaria in patients with SARS-CoV-2 infection [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Unfortunately, not all studies reported the characteristics of the patients studied (gender, age, timing, etc.)…”
Section: Resultsmentioning
confidence: 99%